Potency of Moringa Leaf Extract (Moringa oleifera, Lam.) in Lowering the fatty infiltration of Heart on Hypercholesterolemia Rat (Rattus norvegicus). - Raden Ismail Hafidh Adinugroho; Endang Listyaningsih Suparyanti; Muthmainah Muthmainah (Nexus Biomedika, 2017)
Introduction: The high consumption of high cholesterol foods associated with increased mortality from cardiovascular disease. Because of the side effects like myopathy and the high price of hipercholestrolemia therapy, public interest for the use of natural medicine increased. Moringa leaves contain flavonoids, polyphenols, and ?-sitosterol so that it can reduce fatty infiltration at heart. Histological Study of effect moringa leaves on heart has never been performed before. This study aimed to determine whether the extract of Moringa leaf (Moringa oleifera Lam.) can lower the fatty infiltration of heart on hypercholesterolemia rat model (Rattus norvegicus). Methods: This study was an experimental laboratory with post test only control group design. A sample of male rats were consisting of Sprague Dawley rats, weight 150-200 g, aged 2-3 months. The sampling technique used is incidental sampling. Twenty eight of samples were randomly divided into four groups, each group consisted of 7 rats.Group KK is given aquades. Group K (-), K1, and K2 is given a high-fat diet for 42 days. Group K1 and K2 were each given Moringa leaf extract at a dose of 200 and 400 mg pe kg of body weight from day 42nd until day 70th. Termination was performed on 71th day, then their hearts were prepared for specimen stained with hematoxylin eosin. Heart ventricle fat area was observed with 1000x magnification on light microscope. The data were analyzed using Kruskal-wallis comparative test and then Post-hoc test Mann Whitney was performed (? = 0.05). Results: The observation area of fat at left and right ventricle in KK, K (-), K1, K2 were 378.8153.32; 1280.15133.94; 386.7457.87; and 326.129.89 ?m. Kruskall-Wallis test showed significant result (p = 0.000). Mann Whitney test results showed no statistically significant difference in area of ventricle fat (p <0.05) among all groups, except between groups of KK and K1 (p = 0.633). Conclusion: The extract of leaves of Moringa (Moringa oleifera Lam.) can reduce steatosis / fatty liver histopathology picture rat heart (Rattus norvegicus) model of hypercholesterolemia. Keywords:Moringa leaf extract, heart, fatty infiltration, rat.